EFFECTIVENESS STYLE LINEAR AND NON-LINEAR SETTINGS CERTIFIED IN MATH LEARNING - Iman, Nurul (Universitas Negeri Makassar, 2017)
This study aims to compare the effectiveness of applying linear note style and non linear recording style with scientific setting in terms of learning achievement, mathematical communication, and student self-efficacy. The type of research is quasi experimental research with pretet-posttest nonequivalent comparison-group design design. The population in this research is all students of class VIII SMP Negeri 15 Yogyakarta. The samples are class VIIIE and VIIIB as experimental class. Class VIIIE is treated as linear recording style, while class VIIIB is treated with non linear recording style. To test the effectiveness of learning using paired sample t test. To test the difference in effectiveness using MANOVA (multivariate tests). For univariate test using independent sample t-test. The results of this study are: 1) linear note style effective when viewed from learning achievement and mathematical communication, while non linear note style effective when viewed from student achievement and student self-efficacy. 2) There is a difference of effectiveness between linear and non linear recording style in terms of learning achievement, mathematical communication and student self-efficacy. 3) linear note style is more effective when viewed from learning achievement and mathematical communication, while non linear note style more effective if ditinjasu from self-efficacy student